Management of organizational behavior : leading human resources - Hersey, Paul; Blanchard, Kenneth H.; Johnson, Dewey E. (Delhi : Pearson Education, 2001)
Business
2005-04-19
Keywords: Organizational behavior; Leadership; Behavior; organizational transformation